2017
DOI: 10.1101/157677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Influence of Aging and Mechanical Stretch in Alveolar Epithelium ER Stress and Inflammation

Abstract: Ventilator-Induced lung injury (VILI) is a form of acute lung injury that is initiated or exacerbated by mechanical ventilation. The aging lung is more susceptible to lung injury. Harmful mechanical stretch of the alveolar epithelium is a recognized mechanism of VILI, yet little is known about how mechanical stretch affects aged epithelial cells. An activated response known as Endoplasmic Reticulum (ER) Stress occurs at the cellular level, which is increased with aging. The disrupted ER function results in dis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…It has been well established that ATF4 is a pro-osteogenic transcription factor 8,36 . Valentine et al 60 showed that exposure of mouse type II alveolar epithelial cells (ATII) to 15% stretch resulted in significant increase of ATF4 expression compared to static control. Yang et al 71 reported that 10% stretch significantly upregulated ATF4 expression in human periodontal ligament cells (hPDLCs) compared to static control.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that ATF4 is a pro-osteogenic transcription factor 8,36 . Valentine et al 60 showed that exposure of mouse type II alveolar epithelial cells (ATII) to 15% stretch resulted in significant increase of ATF4 expression compared to static control. Yang et al 71 reported that 10% stretch significantly upregulated ATF4 expression in human periodontal ligament cells (hPDLCs) compared to static control.…”
Section: Discussionmentioning
confidence: 99%